Estetika Oposisi Biner: Analisis Gaya Bahasa Thibaq dalam Surah al-Lail - Syahvika, Nur; Rahman, Abdul (Lembaga Yasin AlSys, 2026)
The beauty of language style in the Qur’an is one of the important aspects of balaghah studies, particularly through the use of thibaq, or semantic opposition, which strengthens the message of the verses. This study aims to reveal the beauty of the thibaq style found in Surah Al-Lail. This study used a qualitative approach with a library research design. The research data were collected from the verses of Surah Al-Lail and analyzed using the theory of ‘Ilm al-Badi’ as one branch of balaghah. The results show that there are several forms of thibaq in Surah Al-Lail, both those that bring together two nouns, such as night and day as well as male and female, and two concepts of human behavior, such as giving charity and being miserly as well as ease and hardship. The use of the thibaq style in this surah functions not only as an aesthetic ornament in the language structure but also as a means of emphasizing meaning that helps readers understand and reflect on two contrasting life choices and their consequences in the hereafter. This study affirms that the analysis of thibaq in Surah Al-Lail can broaden understanding of the rhetorical beauty of the Qur’an and strengthen the study of ‘Ilm al-Badi’ in linguistic and Islamic studies.